Faktor-faktor Penting Daya Tarik Stasiun Radio Bagi Pendengar Radio Di Kota Semarang - Rosalia, Naiza (Interaksi: Jurnal Ilmu Komunikasi, 2012)
Abstract Competition in the radio broadcasting in Semarang make every radio station in Semarang always give something new, they modificate each element or even the format on broadcast radio, but at the end there is element or factor that listener like and dislike. This article will determine what factors are the attractiveness of the radio stations for radio listeners in Semarang so that to radio person will know which factor is the most important one. When radio person know which factor is the most important one then they can fulfil wants and needs their listeners and win the competition Keywords : broadcast, radio, the attractiveness of the radio station